PERILAKU API DAN EMISI PADA PEMBAKARAN DROPLET BIODIESEL DICAMPUR DIETHYL ETHER YANG DIPENGARUHI MEDAN MAGNET - Dony Perdana; Firnanda Sumanjaya Putra (Scientific Journal of Mechanical Engineering Kinematika, 2025)
This research aims to investigate flame behavior and emissions droplet combustion of blend waste cooking oil biodiesel- diethyl ether which is influenced by a magnetic field. The need for energy continues to increase, while fossil fuels are becoming increasingly depleted and non-renewable. Therefore development of renewable energy sources are a necessity, such as alternative fuels made from natural resources, namely waste cooking oil biodiesel. This study uses a direct experimental method of burning waste cooking oil biodiesel droplets with variations in mixture concentrations of 0%, 10%, 15%, and 20% diethyl ether. Two magnetic bars with an intensity of 10000 G are placed between a 0.12 mm diameter with K type thermocouple as a repulsive magnetic field in the south-south direction.. The droplet diameter of blends of waste cooking oil biodiesel and diethyl ether is around 1.2 mm. Results of the study found that the addition of variations of diethyl ether mixtures with concentrations of 0%, 10%, 15%, 20% and a repulsive magnetic field (S-S) had a significant effect on flame evolution, flame height and exhaust gas emissions. The variation of diethyl ether (20%) blends produces of shortest flame time of 592 milliseconds, the lowest flame height of 7.41 mm and NOx exhaust gas emissions with the lowest value of 137 ppm.